Isoprostanoids in Clinical and Experimental Neurological Disease Models - Cinzia Signorini; Claudio De Felice; Jean-Marie Galano; Camille Oger; Silvia Leoncini; Alessio Cortelazzo; Lucia Ciccoli; Thierry Durand; Joussef Hayek; Jetty Chung-Yung Lee (MDPI AG, 2018)
Isoprostanoids are a large family of compounds derived from non-enzymatic oxidation of polyunsaturated fatty acids (PUFAs). Unlike other oxidative stress biomarkers, they provide unique information on the precursor of the targeted PUFA. Although they were discovered about a quarter of century ago, the knowledge on the role of key isoprostanoids in the pathogenesis of experimental and human disease models remains limited. This is mainly due to the limited availability of highly purified molecules to be used as a reference standard in the identification of biological samples. The accurate knowledge on their biological relevance is the critical step that could be translated from some mere technical/industrial advances into a reliable biological disease marker which is helpful in deciphering the oxidative stress puzzle related to neurological disorders. Recent research indicates the value of isoprostanoids in predicting the clinical presentation and evolution of the neurological diseases. This review focuses on the relevance of isoprostanoids as mediators and potential biomarkers in neurological diseases, a heterogeneous family ranging from rare brain diseases to major health conditions that could have worldwide socioeconomic impact in the health sector. The current challenge is to identify the preferential biochemical pathways that actually follow the oxidative reactions in the neurological diseases and the consequence of the specific isoprostanes in the underlying pathogenic mechanisms.